1952
DOI: 10.1017/s0007485300040499
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Aqueous Suspensions of Insecticides. Part III. Factors affecting the Persistence of some Synthetic Insecticides

Abstract: Factors affecting the persistence of deposits from aqueous suspensions of insecticides have been studied.There is an inverse relationship between particle size of insecticides and the initial contact toxicity to mosquitos. The influence of particle size on effectiveness decreases as the intrinsic toxicity of the insecticide increases. The compounds investigated can be arranged in order of immediate contact toxicity to mosquitos (Aëdes aegypti): dieldrin ≥ gamma-BHC > aldrin > DDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1954
1954
1985
1985

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The results at 25 mg. per sq. ft. were similar to those recorded previously (Hadaway & Barlow, 1952) while the higher dosages gave kills which were roughly proportional to dosage. Chemical determinations of the distribution of y BHC in blocks sprayed with 100 mg. per sq.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The results at 25 mg. per sq. ft. were similar to those recorded previously (Hadaway & Barlow, 1952) while the higher dosages gave kills which were roughly proportional to dosage. Chemical determinations of the distribution of y BHC in blocks sprayed with 100 mg. per sq.…”
Section: Methodssupporting
confidence: 89%
“…The striking behaviour of particles of insecticide sprayed on to some tropical soils was described in two previous papers (Hadaway & Barlow, 1952; Barlow & Hadaway, 1955). The particles of insecticide disappeared from the surface of blocks made of the soils kept at normal ambient temperatures and humidities in times ranging from a few hours for y BHC to a few days for DDT.…”
mentioning
confidence: 80%
“…Dieldrin-40 mg. solvent, and Hadaway & Barlow (1952) and also Davidson (1953) have shown that the insecticides are not repellent in the strict sense denned above. The former authors showed that mosquitos confined over, but not touching, deposits of volatile insecticides like BHC and aldrin, which have a pronounced fumigant effect, did not move away until the onset of symptoms that led very soon after to knockdown.…”
Section: Effect On Number Of Mosquitos Enteringmentioning
confidence: 95%
“…Fumigant action is not a likely cause, because in our figures the reduction is much the same with DDT, which has no fumigant effect, as with BHC, which has. Also, fumigant action, at least in the laboratory, is quite slow and may not affect the movements of mosquitos in less than about 20 or 30 minutes' exposure (Hadaway & Barlow, 1952, 1953.…”
Section: Effect On Number Of Mosquitos Enteringmentioning
confidence: 99%
See 1 more Smart Citation